New Insights into the Anti-pathogenic Potential of Lactococcus garvieae against Staphylococcus aureus Based on RNA Sequencing Profiling - Delpech, Pierre; Rifa, Etienne; Ball, Graham; Nidelet, Sabine; Dubois, Emeric; Gagne, Geneviève; Montel, Marie-Christine; Delbès, Céline; Bornes, Stéphanie (Frontiers in Microbiology, 2017)
The bio-preservation potential of Lactococcus garvieae lies in its capacity to inhibit the growth of staphylococci, especially S. aureus, in dairy products and in vitro. In vitro, inhibition is modulated by the level of aeration, owing to hydrogen peroxide (H2O2) production by L. garvieae under aeration. The S. aureus response to this inhibition has already been studied. However, the molecular mechanisms of L. garvieae underlying the antagonism against S. aureus have never been explored. This study provides evidence of the presence of another extracellular inhibition effector in vitro. This effector was neither a protein, nor a lipid, nor a polysaccharide, nor related to an L-threonine deficiency. To better understand the H2O2-related inhibition mechanism at the transcriptome level and to identify other mechanisms potentially involved, we used RNA sequencing to determine the transcriptome response of L. garvieae to different aeration levels and to the presence or absence of S. aureus. The L. garvieae transcriptome differed radically between different aeration levels mainly in biological processes related to fundamental functions and nutritional adaptation. The transcriptomic response of L. garvieae to aeration level differed according to the presence or absence of S. aureus. The higher concentration of H2O2 with high aeration was not associated with a higher expression of L. garvieae H2O2-synthesis genes (pox, sodA, spxA1) but rather with a repression of L. garvieae H2O2-degradation genes (trxB1, ahpC, ahpF, gpx). We showed that L. garvieae displayed an original, previously undiscovered, H2O2 production regulation mechanism among bacteria. In addition to the key factor H2O2, the involvement of another extracellular effector in the antagonism against S. aureus was shown. Future studies should explore the relation between H2O2-metabolism, H2O2-producing LAB and the pathogen they inhibit. The nature of the other extracellular effector should also be determined.